Analyzing the cyberbullying phenomenon on social media from the perspective of students - Bularca, Maria Cristina; Cristescu, Sergiu; Netedu, Adrian; Coman, Claudiu (Frontiers in Psychology, 2024)
IntroductionWith the significant increase in the number of social media users, the degree of cyberbullying has also increased in a directly proportional manner. Cyberbullying manifests itself in the commission of psychological abuses, teenagers being the most vulnerable.MethodsThe purpose of our paper was to analyze how the phenomenon of cyberbullying manifests in terms of frequency on social media platforms, while taking into account factors such as gender, and elements related to the behavior/reactions of witnesses and victims. We conducted a quantitative research, while having as an instrument a questionnaire. We sent the questionnaire online on the Facebook group of students from Transilvania University of Brasov, the sample of the research comprising 500 students. The quantitative method used was considered appropriate for the analysis of this phenomenon because through the questionnaire we were able to gain some insights and a more wide perspective regarding students’ perception about cyberbullying and its prevalence on social media.ResultsThe results of the research showed that respondents were aware of the existence of the phenomenon of cyberbullying on social media, and that the main forms of online bullying they experienced or witnessed referred to: ridiculing people’s physical or intellectual aspects and features, being verbally abused or threatened, being humiliated by posting sensitive content, being excluded from a group, or having their secrets publicly revealed. There were no differences found in the degree of exposure to online bullying according to gender, but the results revealed that undergraduate students, and younger students were more exposed to cyberbullying than master students and students of older age.DiscussionThe findings also highlight the fact that witnesses have an important role in the cyberbullying phenomenon. Thus, even though most of the respondents declared that they did not get involved when they witnessed cyberbullying, this results are relevant to prevention policies because they emphasize the need to develop educational campaigns regarding cyberbullying and the need to promote ethical behavior online. The results highlight the need of raising awareness and of educating young people about the phenomenon of cyberbullying, and the need of finding appropriate ways in which this phenomenon could be detected and prevented. From a theoretical point of view, the paper contributes to the literature on the forms of manifestation of cyberbullying on social media platforms, from the perspective of students. In the context of the practical implications of our paper, the results highlight the need of including information about the phenomenon of cyberbullying in the education of young people, the need of conducting awareness and prevention campaigns or programs. The paper also highlights the need of developing and implementing instruments on social media platforms, that could detect the improper behavior of users.